2018
DOI: 10.4314/jae.v22i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Role of men and women in agro-input business in north west, Nigeria

Abstract: This study examined the role of male and female in agro-inputs entrepreneurship in Introduction:Over the years, attempt to bridge the gap between men and women farmers as well as entrepreneurs in Nigeria, had resulted in the emergence of various women groups and organizations. They have been able to contribute immensely to the gains recorded by women in agricultural and rural development (Adegbidi, 2012). Findings from various studies revealed that women make up 60-80% of agricultural labour force in Nigeria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…Furthermore, the table shows that 44.2 % of the input dealers had tertiary education. This finding is in consonance with Adam (2018) who found that 20.8% agro-input dealers in northwest Nigeria attained tertiary education. It is expected that with their level of education they should be able to provide information to farmers.…”
Section: Socioeconomic Characteristics Of Input Dealerssupporting
confidence: 90%
“…Furthermore, the table shows that 44.2 % of the input dealers had tertiary education. This finding is in consonance with Adam (2018) who found that 20.8% agro-input dealers in northwest Nigeria attained tertiary education. It is expected that with their level of education they should be able to provide information to farmers.…”
Section: Socioeconomic Characteristics Of Input Dealerssupporting
confidence: 90%
“…Respondents' socioeconomic characteristics were measured with the use of descriptive statistics. In determining the level of participation in agrobased income generating activities, some activities each for on-farm and off-farm activities that followed Adam (2018) and report from a reconnaissance survey were generated which was rated on a 3-point Likert type scale of No participation=1, Partial-Participation=2 and High Participation=3, The mean score was determined and the mean score was calculated, Mean below the benchmark was considered as low Participation while those above were considered as high participation.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…It is therefore necessary to assess the level of male and female participation in Agro-based enterprises in Ogun state to identify gaps if any. It is also worth noting that there are many theoretical and empirical studies of different scholars discussing income-generating activities (Adam, 2018;Dickson, Ekpe, and Egbe, 2014;Mtsor and Idisi, 2014;National Bureau of Statistics, 2013). However, most of them are based on an assessment of women's participation in generating incomegenerating enterprises and leave behind other groups in the communities like men and youths.…”
Section: Introductionmentioning
confidence: 99%
“…Data in Table 2 shows that 68.9% of the agro-dealers were male, while only 31.1% were female. Adam revealed that agro-dealers were male profiteering to cater for the wellbeing of their family (Adam, 2018). A study on Gender Responsive Approaches by also indicated that most agro-dealer businesses in Africa are owned by men, but women may be co-owners (Adam et al, 2019).…”
Section: Socio-economic Characteristics Of Agro-dealersmentioning
confidence: 99%